A Hybrid Load Balancing Scheme for Games in Wireless Networks. (28th May 2014) - Kim, Hye-Young; Park, Hwa-Jin; Lee, Seojeong
Abstract : A wireless network consists of a large number of nodes with limited resources. The large number of event data will be generated over a period of time in a wireless network. Also, faced with high resource demand variability and with misfit resource renting policies, the current practices is to overprovision for each game tens of owned data. In a wireless network, the agent node may become easily overloaded by the high demand from the players for updates. So, we propose a hybrid load balancing scheme for games in wireless networks which is based on allocating load on wireless mobile nodes proportionally to each of the agent's capacities. This proposed scheme is a combined dynamic provisioning algorithm based on greedy graph and user-oriented load balancing scheme for maintaining the performance and stability of distributed system in wireless networks. We address the key functions for our proposed scheme and simulate the efficiency of our proposed scheme using mathematical analyses. We then testify that the proposal has best performance compared with previous researches.